The effect of regular chokeberry juice consumption on anthropometric and lipid parameters in women with overweight or obesity - Jana Mrázová; Jana Kopčeková; Marta Habánová; Martina Gažarová; Petra Lenártová (National Institute of Public Health - National Institute of Hygiene, 2024)
Background Aronia melanocarpa is nowadays valued for its high content of biologically active substances, the main group of which are polyphenols, which include anthocyanins, flavonols, flavanols, proanthocyanidins and phenolic acids. From the available sources, we can conclude that extracts and juices from black chokeberry have a great potential in human nutrition and influence on their health. Objective The research was to evaluate the effect of regular consumption of 100% organic chokeberry juice on selected anthropometric and lipid parameters of overweight or obese women. Material and Methods A clinical study consisted of 19 women with overweight and obesity, age from 44 to 63. The probands consumed 50 ml of chokeberry juice daily for 8 weeks as part of their regular diet. Body composition and biochemical indicators were monitored before consumption, after 4 and 8 weeks of nutritional intervention. Body composition was determined using multifrequency bioelectrical impedance analysis (MFBIA) - InBody 720. Biochemical analyzes of blood serum were performed using standard methods in an accredited laboratory using automatic biochemical analyzer a BioMajesty JCA-BM6010/C. Results The monitored group of probands is characterized by menopausale and postmenopausale women, overweight or obese women with hypercholesterolemia without pharmacological treatment. Statistically significant differences (p<0.05) were observed when evaluating the amount of body fat (BFM) of the probands before the start of consumption and after the consumption of chokeberry juice. We noted a statistically significant reduction especially in the assessment of visceral fat (VFA) (p<0.001). There were no fundamentally significant changes in the lipid profile of women in this intervention study. With short-term consumption of chokeberry juice (after 4 weeks), we recorded an average reduction in total cholesterol and LDL-cholesterol, but without statistical significant. We also focused on the evaluation of the inflammatory marker CRP and noted a significant beneficial reduction of CRP (p˂0.05). Conclusions In the research, we evaluated the effect of 8 weeks consumption of 100% chokeberry juice on selected anthropometric parameters, focusing on changes in visceral fat and total fat in overweight and obese women. In conclusion, we can state that the regular consumption of chokeberry juice has a beneficial effect on fat tissue in women of reproductive age, which can reduce the risk of cardiovascular diseases.